KONTROL DIRI, KECERDASAN EMOSI, DAN PERILAKU CYBERBULLYING PENGGUNA AKUN ALTER X (TWITTER) - Aulani, Shafna Dinar; Agustina, Laelatus Syifa Sari (Universitas Gunadarma, 2024)
An interesting phenomenon emerged among X users which is the existence of alter account users. Alter account users are at risk of engaging in cyberbullying behavior since it is difficult to hold them accountable for their actions without a real identity. This study aims to know the relationship between self-control and emotional intelligence with cyberbullying behavior among alter X account users. The participants in this research were 170 people using the alter X account which was determined through convenience sampling techniques. The data obtained was tested by using multiple linear regression analysis. The result shows that there is a significant relationship between self-control and emotional intelligence in cyberbullying behavior. Furthermore, the research results show that there is a significant relationship between self-control and cyberbullying behavior and there is no significant relationship between emotional intelligence and cyberbullying